Effectiveness of Digital Marketing with Influencers, Video Content, and Referral Programmes on Consumer Trust in E-Commerce Platforms in West Java - Tubalawony, Jacsy (West Science Social and Humanities Studies, 2024)
This study examines the efficacy of digital marketing methods, particularly influencer marketing, video content, and referral programs, on consumer trust in e-commerce platforms in West Java. A quantitative research design was utilized to collect data from 300 respondents through a structured online questionnaire. The investigation employed Structural Equation Modeling with Partial Least Squares (SEM-PLS 3) to examine the links between digital marketing methods and consumer trust. The results indicate that all three tactics markedly improve consumer trust, with influencer marketing exerting the greatest influence. These findings provide significant insights for e-commerce enterprises aiming to enhance their digital marketing strategies and cultivate more robust consumer relationships. The study enhances comprehension of customer behavior in the digital marketplace and offers practical ideas for improving consumer trust in e-commerce.